Housing Finance Snags Faced by Indian Home Loan Mortgagors : A Matter-of-Fact Study - Srinivasa Kumar, D. (Indian Journal of Finance, 2017)
Housing is an essential need in each economy and it is a fundamental pointer for the financial improvement of the nation. This study distinguished the problems faced by home loan borrowers from the application stage to the last stage of loan repayment and examined how their socio - financial profile impacted their perceptions of the problems faced by them while availing home loans. This paper revealed that the salaried class faced problems like the documents needed for screening, rate of interest, and time gap between loan applied and sanctioned ; while the self-employed class individuals faced problems like filling up the application form, gap between loan applied and sanctioned, and documents needed for screening. The critical contrasts seen amongst salaried and self-employed respondents were : filling up the application form, time gap between loan applied and sanctioned, transparency screening, and EMI in light of the t - values.